People Japanese: an interactive multimedia courseware using human-centred design approach / Muhammad Hasif Muhamed Asri - Muhamed Asri, Muhammad Hasif (2015)
Learning education has become more interesting and interactive for students due to rapid development of interactive multimedia courseware. It is one of tools to support the growth of language learning in perspective of learner of the language. The problem statement is using manual book to learn Japanese language lead to users getting bored and having hard time learning due to limited capability of satisfying learning environment such as less colour representation of the book, hard to navigate content of the book, consume lots of time when navigating the content of the book, and hard to demonstrate the related topic of the language learning. The aim is to develop an interactive multimedia courseware which helps users to learn Japanese language and cultural background knowledge using the human-centred design approach. The objectives are to analyse and compare the suitable guidelines for designing the interactive multimedia courseware, to design and develop the prototype of the interactive multimedia courseware, and to evaluate the prototype in order to assess its usability and learning outcomes. Methodology used is human-centred design approach. The usability testing result shows that aspect of satisfaction was the highest and it shows that the users were satisfied using the courseware. The learning outcomes assessment result shows that average of learning outcomes using courseware was higher than average of learning outcomes using manual book. It can be concluded that using the courseware is better than using the manual book in term of the learning outcomes.